1990
DOI: 10.1901/jaba.1990.23-539
|View full text |Cite
|
Sign up to set email alerts
|

Gender Factors in Reviewer Recommendations for Manuscript Publication

Abstract: This study investigated whether the gender of manuscript authors affected reviewers' editorial decisions. Female and male reviewers for five behavioral journals were asked to evaluate identical manuscripts according to their usual criteria. Half the manuscripts were supposedly written by men and half by women. Male reviewers did not evaluate male- and female-authored manuscripts differently. Female reviewers accepted significantly more female-authored (62%) than male-authored (10%) manuscripts. Female-authored… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
65
1
3

Year Published

1994
1994
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(72 citation statements)
references
References 8 publications
3
65
1
3
Order By: Relevance
“…13 Gender bias, the differential handling of a manuscript based on the gender of the author, editor, or reviewer, may be a component of the second, or publication, phase. Some literature focuses on the association between reviewer gender and reviewer recommendations, 14,15 and we sought to define the behavioral differences of the editorial board members of this journal using data from its web-based manuscript review system. This system was implemented by Obstetrics and Gynecology in 2002 and provided a ready resource.…”
Section: Discussionmentioning
confidence: 99%
“…13 Gender bias, the differential handling of a manuscript based on the gender of the author, editor, or reviewer, may be a component of the second, or publication, phase. Some literature focuses on the association between reviewer gender and reviewer recommendations, 14,15 and we sought to define the behavioral differences of the editorial board members of this journal using data from its web-based manuscript review system. This system was implemented by Obstetrics and Gynecology in 2002 and provided a ready resource.…”
Section: Discussionmentioning
confidence: 99%
“…Social and publication biases: Although often idealized as impartial, objective assessors, in reality studies suggest that peer reviewers may be subject to social biases on the grounds of gender ( Budden et al , 2008; Lloyd, 1990; Tregenza, 2002), nationality ( Daniel, 1993; Ernst & Kienbacher, 1991; Link, 1998), institutional affiliation ( Dall’Aglio, 2006; Gillespie et al , 1985; Peters & Ceci, 1982), language ( Cronin, 2009; Ross et al , 2006; Tregenza, 2002) and discipline ( Travis & Collins, 1991). Other studies suggest so-called “publication bias”, where prejudices against specific categories of works shape what is published.…”
Section: Introductionmentioning
confidence: 99%
“…The evidence on whether there is bias in peer review against certain author demographics is mixed, but overwhelmingly in favor of systemic bias against women in article publishing ( Budden et al , 2008; Darling, 2015; Grivell, 2006; Helmer et al , 2017; Kuehn, 2017; Lerback & Hanson, 2017; Lloyd, 1990; McKiernan, 2003; Roberts & Verhoef, 2016; Smith, 2006; Tregenza, 2002) (although see also Blank (1991); Webb et al (2008); Whittaker (2008)). After the journal Behavioural Ecology adopted double blind peer review in 2001, there was a significant increase in accepted manuscripts by women first authors; an effect not observed in similar journals that did not change their peer review policy ( Budden et al , 2008).…”
Section: The Traits and Trends Affecting Modern Peer Reviewmentioning
confidence: 99%